Sulfasalazine-Induced Epstein–Barr Virus-Positive Mucocutaneous Ulcer - Cedric Stabel; F. J. Sherida H. Woei-A-Jin; Thomas Tousseyn; Maria Garmyn (Case Reports in Hematology)
Epstein–Barr virus (EBV) may cause a wide spectrum of symptomatology in humans ranging from asymptomatic upper respiratory tract infection to infectious mononucleosis and in more severe cases lymphoproliferative disorders or hemophagocytic lymphohistiocytosis. Its neoplastic potential is higher in immunocompromised individuals. We describe a case of EBV-positive mucocutaneous ulcer, a more indolent clinical entity on the spectrum of EBV-driven lymphoproliferative disorders, and are one of the first to put sulfasalazine, an immunomodulatory agent, forward as the possible culprit.